Reflections on Finalizing an Economic Partnership Agreement: The EAC with the EU - Jaime de Melo; Julie Regolo (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
This paper appraises the likely effects of the EPA agreement the EAC is about to sign with the EU. Customs data are used to estimate the revenue and welfare effects of finalizing an EPA agreement. The estimates show that because of exemptions, estimates from the usual approach of relying on statutory are cut in half.While the gains to consumers and producers would not completely offset the loss in revenues , they are very small contributing only to 0.1% of initial (total) import expenditures for Rwanda and of 0.2% for Uganda. The paper then discusses the benefits that would occur if the long and complex EU-EAC protocol on Rules of Origin were simplified and made more compatible with the multilateral trading system. An inclusion of Services would have been desirable and the time table for tariff reduction in the EAC should be shortened.
Keywords: F13; O19; 330